ETHICS, EXPERIENCE, AND GOVERNMENT PROCUREMENT OVERSIGHT: DISCIPLINE AND SATISFACTION AS MEDIATORS - Egi Kurniawan; Suhanda Suhanda (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
Effective oversight of government procurement remains a significant challenge in the public sector. This study investigates the effects of ethics and work experience on procurement oversight performance in the West Sumatra Provincial Government, with job satisfaction and work discipline examined as mediating variables. Using a quantitative research design, data were collected through 62 valid questionnaires and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The study findings reveal that ethics do not directly improve oversight performance unless mediated by job satisfaction, while work experience significantly influences oversight performance both directly and through job satisfaction. Job satisfaction emerges as the most dominant predictor, significantly mediating the effects of ethics and experience on performance. Work discipline, although positively influenced by ethics and satisfaction, does not significantly contribute to oversight outcomes, either directly or as a mediator. These results emphasize the central role of psychological and attitudinal factors—especially job satisfaction—in shaping the effectiveness of public sector audits. This study contributes to the literature on public procurement oversight by offering empirical support for attribution theory and the behavioral dimensions of human capital. Policy implications include prioritizing efforts to improve ethics, experience, and job satisfaction rather than relying solely on law enforcement-based disciplinary approaches. JEL Classification: H57, M42, D73, J28, O15 Keywords: Procurement Oversight, Ethics, Work Experience, Job Satisfaction, Work Discipline, Public Sector